(untitled) (Research, Society and Development, 2019)
This article aims to know the contribution of the academy to the teaching course focusing on the dilemmas and challenges of teachers who experience the profession in the early years of basic education. The authors who support the study discuss teacher training involving teacher knowledge, initial and vocational training, professional dilemmas, reflexive teacher and professional identity. The methodology used was the Training Narratives, which works punctually with personal and collective paths of educators. The results showed that the interviewed subjects, when coming in contact with the theoretical contributions and with the stage, experienced difficulties that extended until the beginning of their career. However, living together in a collaborative environment of learning and exchanging experiences, gradually instrumented them to face the challenges inherent in the profession. Therefore, the results pointed out that the subjects are aware of the challenges of the profession and realize the importance of the reflection on the practice so that it reaches the meanings of its profession and sees itself as producer of knowledge as agent of human interactions.